Culture and Health in Anti-Aging Medicine Practice in Surabaya City - Chandra, Imelda Audry (Green Publisher Indonesia, 2025)
Aging, traditionally revered in Javanese culture, is increasingly juxtaposed with globalized anti-aging medicine in urban Indonesia. Surabaya, a city blending modernity and tradition, exemplifies this tension, yet limited research explores its cultural dynamics. This study examines how Surabaya’s residents perceive anti-aging practices amid Javanese cultural values, focusing on generational divides, gendered pressures, and the interplay of traditional and modern medicine.The research used a qualitative case study with a phenomenological approach was employed, combining in-depth interviews (15 clients, 10 practitioners) and participant observations in three anti-aging clinics. Data were analyzed thematically to identify cultural and social patterns. While Javanese culture venerates aging as wisdom, Surabaya’s middle class increasingly adopts anti-aging therapies (e.g., Botox, hormone therapy) to meet beauty standards, particularly among women facing professional and social pressures. Traditional remedies like jamu coexist with modern treatments, reflecting adaptive cultural hybridity. Generational conflicts emerged, with youth prioritizing aesthetics and elders valuing natural aging. The study highlights the need for culturally sensitive health policies to address social inequalities in access and preserve respect for aging amid medicalization. It calls for further research on gender-specific impacts and comparative urban studies in Indonesia.